2013
DOI: 10.1371/journal.pone.0053542
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions and Properties of an Exopolysaccharide from Klebsiella sp. H-207 and Application in Adsorption of Hexavalent Chromium

Abstract: The novel exopolysaccharide HZ-7 is produced by Klebsiella sp. H-207, and its fermentation conditions were optimized by response surface methodology (RSM). In this study, the optimized medium consisted of sucrose 31.93 g/L, KNO3 2.17 g/L and K2HPO4 5.47 g/L; while the optimized culture conditions consisted of seed age 13 h, with an inoculum size of 10.6% and incubation temperature of 28.9°C. A maximum HZ-7 yield of about 15.05 g/L was achieved under the optimized conditions using RSM and single-factor experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The Response Surface Methodology (RSM) with Box-Behnken design (BBD) was employed to determine the optimal values of selected parameters. It was proved, that this methodology is an effective tool for prediction of optimal process condition for multiple parameter systems [31] [33] . The respective levels with the coded levels for the factors are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 96%
“…The Response Surface Methodology (RSM) with Box-Behnken design (BBD) was employed to determine the optimal values of selected parameters. It was proved, that this methodology is an effective tool for prediction of optimal process condition for multiple parameter systems [31] [33] . The respective levels with the coded levels for the factors are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 96%
“…Compact EPSs produced by M. algicola MB-44 and H. hydrothermalis MB-45 were found to be amine-substituted. While compact structure of EPS indicated its potential to be used as viscosifier, thickener or stabilizing agent for use in food industry because of plasticized film like property (Sajna et al 2013); porous EPS structure were proven to be a good candidate for heavy metal biosorption (Qiang et al 2013), while also having the capillary force to hold more water (Rani et al 2017). The fibrous pores of bacterial EPSs were already proved to help bacterial cells to stay attached to each other due to high affinity interactions (Rani et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the highest EPS production of the strain in the sucrose containing medium. Qiang et al (18) 4 , and NaNO 3 ) were studied to define an optimal medium. A significant increase in the levan yield from 5.27 up to 15.42 g.L -1 under these conditions was found (19).…”
Section: Discussionmentioning
confidence: 99%